“I won’t always ask”: Complicating Agency in Octavia Butler’s Fledgling - Bast, Florian (Current Objectives of Postgraduate American Studies, 2012)
This study reads Octavia Butler’s Fledgling“ as a narrative of agency. Critically engaging previous scholarly tendencies to focus solely on the main protagonist’s successful struggle for self-determination, this essay investigates the ways in which Fledgling complicates and irritates simplistic notions of agency, as the novel questions both the possibility and desirability of a high level of agency.